2016
DOI: 10.1371/journal.pone.0147328
|View full text |Cite
|
Sign up to set email alerts
|

ESA Hyporesponsiveness Is Associated with Adverse Events in Maintenance Hemodialysis (MHD) Patients, But Not with Iron Storage

Abstract: ObjectiveIt has been reported that hyporesponsiveness to erythropoiesis-stimulating agent (ESA) is associated with adverse events in patients on maintenance hemodialysis (MHD). However, it has not been determined whether higher iron storage is associated with an improved response, including better survival, to ESA.Design and MethodWe measured serum ferritin, hemoglobin (Hb), and transferrin saturation (TSAT) levels every three months for two years in 1,095 MHD patients. The weekly dose of ESA to Hb ratio was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 32 publications
0
17
1
Order By: Relevance
“…A recent study examined the relationship between iron markers, such as transferrin saturation and ferritin levels, and ESA responsiveness. Finding from the study highlighted that transferrin saturation, but not ferritin, was statistically associated to ESA hyporesponsiveness [20]. On the hand, in our study, transferrin saturation covariate was excluded from the analysis, due to the high proportion of missing values (> 50%).…”
Section: Discussionmentioning
confidence: 84%
“…A recent study examined the relationship between iron markers, such as transferrin saturation and ferritin levels, and ESA responsiveness. Finding from the study highlighted that transferrin saturation, but not ferritin, was statistically associated to ESA hyporesponsiveness [20]. On the hand, in our study, transferrin saturation covariate was excluded from the analysis, due to the high proportion of missing values (> 50%).…”
Section: Discussionmentioning
confidence: 84%
“…Although we did not evaluate hepcidin levels in this study, we have previously reported that serum hepcidin levels in MHD patient are significantly higher than those of healthy volunteers, and serum hepcidin in these patients was closely associated with serum ferritin levels [17]. Moreover, elevated serum hepcidin levels in chronic kidney disease patients (not on dialysis) with <TSAT 20% and ferritin levels �40 ng/mL have been reported [18]. Therefore, it is possible that serum hepcidin levels in patients with dysutalization iron for erythropoiesis might be higher than in other patient groups.…”
Section: Iron Utilization For Erythropoiesis and Adverse Events In Hmmentioning
confidence: 75%
“…The Drive study [7] reported that iron administration in patients with dysutilization of iron for erythropoiesis might attenuate the responsiveness to ESA and increase Hb levels. However, we have previously reported that, among patients with hyporesponsiveness to ESA and patients with higher ferritin level (>100 ng/mL), those treated with higher doses of intravenous iron showed a higher risk of composite events (e.g., CCVD, infection, hospitalization, and death) [18]. We recently demonstrated that a high risk of death and/or adverse events was associated with a consistently high ferritin level, large fluctuations in ferritin levels and high doses of intravenous iron [9] in MHD patients.…”
Section: Iron Administration In Patients With Dysutalization Of Iron mentioning
confidence: 92%
“…Several studies have demonstrated an association between EPO hyporesponsiveness and poor clinical outcomes, such as anemia, heart failure, and increased cardiovascular and all-cause mortality [11, 12]. The ERI is a sensitive evaluation index of EPO responsiveness and can predict composite events (CVD, infection, hospitalization, or death) [13] and all-cause mortality in MHD patients [14, 15]. Our study demonstrated that ERI values were from 2.26 to 32.61 IU/week (g/dL) –1 /kg, and the mean ERI value was (12.67 ± 6.17) IU/week (g/dL) –1 /kg.…”
Section: Discussionmentioning
confidence: 99%